The Profile of Students’ Critical Thinking Measured through Science Virtual Test on 9th Grade in The Theme of Living Things and Environmental Sustainability - R. Auliya Ulul 'ilmi Fernandi; Harry Firman; Lilit Rusyati (Journal of Science Learning, 2017)
The aims of this study are: (1) to investigate the level students’ critical thinking skill on living things and environmental sustainability theme, (2) to examine the critical thinking difference among different gender, learning styles, and students’ motivation, and (3) to investigate the correlation between students’ critical thinking and students’ motivation. This research was conducted due to the importance of critical thinking evaluation or measurement to get current skill description as the basic information to improve critical thinking in junior high school. The method of this study was descriptive research method. 110 students from three junior high school in Kuningan was tested with Science Virtual Test on Living Things and Environmental Sustainability Theme for 9th Grade as the measurement tool of critical thinking based on Inch critical thinking elements, and are given learning style questionnaire and science motivation questionnaire. Generally, the mean scores on six elements and overall critical thinking score from descriptive statistics shows a moderate critical thinking attainments level, with the range 43.33  score 69.75, while other two elements shows low critical thinking attainments level (score  43.33). At significant level 0.05 there is no significant difference between male and female, and also there is no significant difference among visual, aural, read/write, and kinesthetic learning style in critical thinking, while significant difference is founded on three different students’ motivation (Low, Moderate, High) groups on four critical thinking element skills. Hence to support the tendency, the correlation test is conducted. The correlation test shows there is no correlation between critical thinking and students’ motivation (r = 0.155, p = 0.81).